Bi-allelic GAD1 variants cause a neonatal onset syndromic developmental and epileptic encephalopathy. - Chatron, Nicolas; Becker, Felicitas; Morsy, Heba; Schmidts, Miriam; Hardies, Katia; Tuysuz, Beyhan; Roselli, Sandra; Najafi, Maryam; Alkaya, Dilek Uludag; Ashrafzadeh, Farah; Nabil, Amira; Omar, Tarek; et al. (Brain, 2020)
Developmental and epileptic encephalopathies are a heterogeneous group of early-onset epilepsy syndromes dramatically impairing neurodevelopment. Modern genomic technologies have revealed a number of monogenic origins and opened the door to therapeutic hopes. Here we describe a new syndromic developmental and epileptic encephalopathy caused by bi-allelic loss-of-function variants in GAD1, as presented by 11 patients from six independent consanguineous families. Seizure onset occurred in the first 2 months of life in all patients. All 10 patients, from whom early disease history was available, presented with seizure onset in the first month of life, mainly consisting of epileptic spasms or myoclonic seizures. Early EEG showed suppression-burst or pattern of burst attenuation or hypsarrhythmia if only recorded in the post-neonatal period. Eight patients had joint contractures and/or pes equinovarus. Seven patients presented a cleft palate and two also had an omphalocele, reproducing the phenotype of the knockout Gad1-/- mouse model. Four patients died before 4 years of age. GAD1 encodes the glutamate decarboxylase enzyme GAD67, a critical actor of the γ-aminobutyric acid (GABA) metabolism as it catalyses the decarboxylation of glutamic acid to form GABA. Our findings evoke a novel syndrome related to GAD67 deficiency, characterized by the unique association of developmental and epileptic encephalopathies, cleft palate, joint contractures and/or omphalocele.
Keywords: Abnormalities, Multiple; Epileptic Syndromes; Female; Glutamate Decarboxylase; Humans; Infant, Newborn; Male; Mutation; Pedigree

Dual Molecular Effects of Dominant RORA Mutations Cause Two Variants of Syndromic Intellectual Disability with Either Autism or Cerebellar Ataxia. - Guissart, Claire; Latypova, Xénia; Rollier, Paul; Khan, Tahir N; Stamberger, Hannah; McWalter, Kirsty; Cho, Megan T; Kjaergaard, Susanne; Weckhuysen, Sarah; Lesca, Gaetan; Besnard, Thomas; Õunap, Katrin; et al. (Am J Hum Genet, 2018)
RORα, the RAR-related orphan nuclear receptor alpha, is essential for cerebellar development. The spontaneous mutant mouse staggerer, with an ataxic gait caused by neurodegeneration of cerebellar Purkinje cells, was discovered two decades ago to result from homozygous intragenic Rora deletions. However, RORA mutations were hitherto undocumented in humans. Through a multi-centric collaboration, we identified three copy-number variant deletions (two de novo and one dominantly inherited in three generations), one de novo disrupting duplication, and nine de novo point mutations (three truncating, one canonical splice site, and five missense mutations) involving RORA in 16 individuals from 13 families with variable neurodevelopmental delay and intellectual disability (ID)-associated autistic features, cerebellar ataxia, and epilepsy. Consistent with the human and mouse data, disruption of the D. rerio ortholog, roraa, causes significant reduction in the size of the developing cerebellum. Systematic in vivo complementation studies showed that, whereas wild-type human RORA mRNA could complement the cerebellar pathology, missense variants had two distinct pathogenic mechanisms of either haploinsufficiency or a dominant toxic effect according to their localization in the ligand-binding or DNA-binding domains, respectively. This dichotomous direction of effect is likely relevant to the phenotype in humans: individuals with loss-of-function variants leading to haploinsufficiency show ID with autistic features, while individuals with de novo dominant toxic variants present with ID, ataxia, and cerebellar atrophy. Our combined genetic and functional data highlight the complex mutational landscape at the human RORA locus and suggest that dual mutational effects likely determine phenotypic outcome.
Keywords: Adolescent; Adult; Aged, 80 and over; Alleles; Animals; Autistic Disorder; Brain; Cerebellar Ataxia; Child; Child, Preschool; Disease Models, Animal; DNA Copy Number Variations; Female; Genes, Dominant; Genetic Complementation Test; Humans; Intellectual Disability; Larva; Magnetic Resonance Imaging; Male; Middle Aged; Mutation, Missense; Nuclear Receptor Subfamily 1, Group F, Member 1; Purkinje Cells; Syndrome; Zebrafish